Expansion of Reliance Retail - Reliance Industries Limited (2022)
Reliance Retail is ranked second-fastest growing retailer in the world in Deloitte’s 2021 Global 250 list of World’s Largest Retailers. Reliance Retail expands its footprint by: • Launching 7-Eleven® convenience stores in India • Partnering with India’s leading designers Ritu Kumar, Manish Malhotra and Anamika Khanna • Launching JioMart Digital, the new merchant business for Consumer Electronics • Foraying into ultra-premium grocery segment in India with launch of Freshpik.